Spatiotemporal dynamics of geomorphology, landuse, and storm surge inundation of FDMN settled in Bhasan Char island using geo-spatial techniques - Mubtasim Ishraq Antoo; Md. Bodruddoza Mia; Md. Asif Hasan; Mahfuzur Rahman Khan; Pavel Khan; Tareq Chowdury; Anupom Hasib Rose; Kazi Matin Uddin Ahmed (Heliyon)
Bhasan Char has undergone noteworthy transformations in its geographical characteristics since its emergence in 2003. Driven by sediment transported by the Ganges-Brahmaputra-Meghna river system, the island has gradually transitioned from a stretched-out configuration to a more rounded shape primarily due to continuous accretion, while erosion has been minimal since 2012. Currently, the island is being prepared to accommodate over 1 million Forcefully Displaced Myanmar Nationals (FDMN) refugees. This investigation, conducted over the time frame spanning from 2003 to 2023, utilizes multi-temporal satellite imagery to scrutinize the altering geography of the island, encompassing the processes of erosion and accretion, modifications in the coastline, and changes in land utilization and coverage influenced by seasonal variations. By employing the Advanced Land Observing Satellite (ALOS)/Phased Array Type L-Band Synthetic Aperture Radar (PALSAR), the study pioneers an evaluation of storm surge risks that are specific to this island. Additionally, the research utilizes water indices to understand the seasonal geomorphic dynamics of the island and performs a supervised classification to assess land utilization and coverage alterations. The inundation map shows accretion in the north and erosion in the south and southeast. Southwest is the most stable area with the majority population. After the 'Ashrayan -3′ project, significant land use and land cover changes occurred, including urbanization, embankment construction, and agricultural modifications. The average elevation of the island is 2.84 m above sea level, with a risk of inundation from storm surges exceeding 3 m. Rehabilitated populations are particularly threatened if the embankment height of 4.8 m is surpassed. The study's outcomes indicate that other projects worldwide might use the island restoration efforts as a model. This emphasizes how crucial it is to keep an eye on changes in land cover and use for upcoming planning and adaptation initiatives. Moreover, it highlights the necessity of proper assessments of storm surge hazards to guarantee the security and longevity of island communities.